Maslahah Perspective in the Distribution of Shared Wealth: Analysis of Judge's Decision Number 584/Pdt.G/2021/PA.Pwr - Widiyanto, Hari; Muhajir, Muhajir; Khasanah, Fitrohtul; Karimullah, Suud Sarim (Jurnal Keislaman, 2024)
This study aims to analyze the implications and relevance of the perspective of maslahah in legal practice related to the division of common property in the context of the judge's Decision Number 584/Pdt.G/2021/PA.Pwr. This study uses the method of document analysis to analyze the judge's Decision Number 584/Pdt.G/2021/PA.Pwr and related legal contexts. The study's findings indicate that the perspective of maslahah has significant implications for the division of common property. In the decision of Judge Number 584/Pdt.G/2021/PA.Pwr, maslahah perspective is reflected in determining the ratio of 1/3 and 2/3 for the plaintiff and defendant. This decision can be interpreted as an attempt to achieve a fair division and consider each party's contribution in acquiring and maintaining the common property during the marriage or relationship. In addition, the perspective of maslahah is relevant in ensuring wisdom in the division of common property. Considering financial and non-financial contributions, financial needs and capabilities, and the children's best interests are important factors in achieving fair and sustainable distribution. Judge's decision Number 584/Pdt.G/2021/PA.Pwr. The PWR is believed to have considered these factors in maintaining fairness and discretion in the division of common property.